7T MRI‐Histologic Correlation Study of Low Specific Absorption Rate T2‐Weighted GRASE Sequences in the Detection of White Matter Involvement in Multiple Sclerosis. Issue 3 (21st April 2015) - Bagnato, Francesca; Hametner, Simon; Pennell, David; Dortch, Richard; Dula, Adrienne N.; Pawate, Siddharama; Smith, Seth A.; Lassmann, Hans; Gore, John C.; Welch, Edward B.
ABSTRACT BACKGROUND The high value of the specific absorption rate (SAR) of radio‐frequency (RF) energy arising from the series of RF refocusing pulses in T2‐weighted (T2‐w) turbo spin echo (TSE) MRI hampers its clinical application at 7.0 Tesla (7T). T2‐w gradient and spin echo (GRASE) uses the speed from gradient refocusing in combination with the chemical‐shift/static magnetic field (B0) inhomogeneity insensitivity from spin‐echo refocusing to acquire T2‐w images with a limited number of refocusing RF pulses, thus reducing SAR. OBJECTIVES To investigate whether low SAR T2‐w GRASE could replace T2‐w TSE in detecting white matter (WM) disease in MS patients imaged at 7T. METHODS The .7 mm3 isotropic T2‐w TSE and T2‐w GRASE images with variable echo times (TEs) and echo planar imaging (EPI) factors were obtained on a 7T scanner from postmortem samples of MS brains. These samples were derived from brains of 3 female MS patients. WM lesions (WM‐Ls) and normal‐appearing WM (NAWM) signal intensity, WM‐Ls/NAWM contrast‐to‐noise ratio (CNR) and MRI/myelin staining sections comparisons were obtained. RESULTS GRASE sequences with EPI factor/TE = 3/50 and 3/75 ms were comparable to the SE technique for measures of CNR in WM‐Ls and NAWM and for detection of WM‐Ls. In all sequences, however, identification of areas with remyelination, Wallerian degeneration, and gray matter demyelination, as depicted by myelin staining, was not possible. CONCLUSIONS T2‐w GRASE images may replace T2‐w TSE for clinical use. However, even at 7T, both sequences fail in detecting and characterizing MS disease beyond visible WM‐Ls.